ENHANCING MSME COMPETITIVENESS THROUGH ECONOMIC EDUCATION AND GREEN KNOWLEDGE - Oki Anggraeni; Aniek Hindrayani; Mintasih Indriayu (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make a significant contribution to economic growth, yet their competitiveness is often hindered by limited access to knowledge and external support. Existing research rarely integrates environmentally friendly knowledge, economic education, and competitiveness in explaining access to knowledge. This study aims to examine the influence of these variables on external support and access to knowledge in the digital era. This study employs a mixed-methods approach with a sequential explanatory design. This study involved 30 SME operators in Banyumas Regency, Central Java, selected through purposive sampling. Data were collected via questionnaires and interviews, and analyzed using multiple regression and thematic analysis. The results indicate that all variables simultaneously have a significant influence F-value of 38.215 was obtained with a significance level of 0.002, which is less than 0.05. Partially, competitiveness had the strongest influence t-value of 3.214 with a significance level of 0.005, indicating a positive and significant influence, followed by economic education variable yielded a t-value of 2.587 with a significance level of 0.006, indicating a positive and significant effect and green knowledge variable has a t-value of 2.145 with a significance level of 0.004, which is below the 0.05 threshold. These findings indicate that competitiveness enhances access to partnerships and resources, economic education improves decision-making capacity, and green knowledge expands external networks. This study highlights the importance of integrating sustainability knowledge, economic capabilities, and competitiveness to strengthen SMEs. These findings suggest that a comprehensive strategy combining green practices, economic literacy, and digital adaptation is essential for improving access